2014
DOI: 10.1016/j.jare.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, biochemical and histometric responses of Nile tilapia (Oreochromis niloticus L.) by dietary organic chromium (chromium picolinate) supplementation

Abstract: Chromium has been recognized as a new and important micro-nutrient, essential for both human and animal nutrition. This study was conducted to evaluate the appropriateness and/or the use of safety level of dietary chromium picolinate (Cr-Pic), and its effects on the physiological responses, the histometric characteristics, and the chemical analysis of dorsal muscles of mono-sex Nile tilapia, Oreochromis niloticus. A total of 420 fingerlings (28.00 ± 0.96 g) were randomly distributed into 21 fiberglass tanks re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…The experimental diet with concentration 1.55 mg kg -1 Cr +3 had the lower peak and need a shorter time to be accomplished than the other diets, and it was the optimal level of Cr +3 in the diet to transfer the blood glucose into target cells. This is consistent with the research results of Mehrim (2014), in which blood glucose of tilapia (O. niloticus) at low (127 mg dL -1 ) when fed containing chromium picolinate optimal of 400 ppb. Then levels of chromium carbochelate were 18 and 36 mg kg -1 in the diet decreased blood glucose significantly in pacu, Piaractus mesopotamicus after 24 and 48 hours of feeding (De Castro et al 2014).…”
Section: Respiratory Quotient and Ammonia Excretionsupporting
confidence: 92%
See 2 more Smart Citations
“…The experimental diet with concentration 1.55 mg kg -1 Cr +3 had the lower peak and need a shorter time to be accomplished than the other diets, and it was the optimal level of Cr +3 in the diet to transfer the blood glucose into target cells. This is consistent with the research results of Mehrim (2014), in which blood glucose of tilapia (O. niloticus) at low (127 mg dL -1 ) when fed containing chromium picolinate optimal of 400 ppb. Then levels of chromium carbochelate were 18 and 36 mg kg -1 in the diet decreased blood glucose significantly in pacu, Piaractus mesopotamicus after 24 and 48 hours of feeding (De Castro et al 2014).…”
Section: Respiratory Quotient and Ammonia Excretionsupporting
confidence: 92%
“…This condition caused the decreasing of hemoglobin (Hb) in sangkuriang, C. gariepinus when it was fed by the chromium compared to the non-chromium in the diet (Hastuti and Subandiyono 2011). Chromium level was too high also reduce the level of hemoglobin and the number of erythrocytes on tilapia, O. niloticus (Mehrim 2014). The decrease in supplying Fe +3 causes the interference in the process of energy oxidation.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the positive effect of Cr on fat, glucose and protein metabolism, distinguished toxicological features were also there (Aslam & Yousafzai, 2017). Obtained results were deviating from Mehrim (2014) conclusions. Contradictory to the positive effect of Cr supplementation on growth (Seluck et al, 2010) demonstrated that Cr picolinate supplementation have no significant impact on growth and metabolism of fish.…”
Section: Resultsmentioning
confidence: 75%
“…Additionally, medicine herbs (Asimi and Sahu, 2013;Khalil et al, 2014Khalil et al, , 2015Mehrim et al, 2014Mehrim et al, , 2019b and exogenous enzymes (Ayhan et al, 2018;Zheng et al, 2019) were determined. Among other feed additives for fish, the organic acids and their salts were reported (Hossain et al, 2007;Khajepour & Hosseini, 2012;Khaled, 2015) whereas some researchers mentioned the use of minerals (Morken et al, 2011;Mehrim, 2012Mehrim, , 2014.…”
mentioning
confidence: 99%